PENGUKURAN KETINGGIAN MUKA AIR PADA LAHAN GAMBUT MEMPERGUNAKAN SENSOR ULTRASONIK HCSR-04 - Novianti Novianti; Lazuardi Umar (Universitas Riau, 2021)
Indonesia is a country that has an area of + 14 million hectares of peatlands. Utilization of Indonesia's peatlands is used in various sectors such as plantation and agriculture which increase income in the economic sector so the importance of peatland management. Measurement of the water level in peat is very necessary to maintain the stability of the TMA (water level) of the peat, which is 40 cm. This study uses the ultrasonic sensor HCSR-04 which has a resolution of 0.3 cm with a measurement range of 2 cm to 4 m and is coupled with the Arduino Unowhich is open source so that measurements can be carried out directly using the serial monitor on Arduino-uno. The ultrasonic sensorHCSR-04 is made on a prototype that will be used in TMA measurements both in the field and on a laboratory scale. The measurements show very accurately results with measurement errors 1.2 % with measurements from 100 – 500 mm. measurement error for water temperature variations of 30 ºC, 35 ºC,and 40 ºC is 1.8%, 6% and than 10%.